2014
DOI: 10.1039/c4ra02978j
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the photothermal effect of gold nanostars and nanorods for biomedical applications

Abstract: Photothermal properties of GNSs and GNRs are compared both experimentally and theoretically, and results show that GNSs exhibit a higher molar heating rate than GNRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 52 publications
3
74
0
Order By: Relevance
“…Alternatively, the photothermal figure of merit of a colloidal solution can be suitably described by the molar heating rate (MHR) [27] which is defined as the temperature growth rate divided by the molar concentration of Au. In our case, the best fitting of the temperature kinetic recorded at 1 Wcm −2 NIR intensity (Figure 1D), gives an initial growth rate of 0.2°C s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the photothermal figure of merit of a colloidal solution can be suitably described by the molar heating rate (MHR) [27] which is defined as the temperature growth rate divided by the molar concentration of Au. In our case, the best fitting of the temperature kinetic recorded at 1 Wcm −2 NIR intensity (Figure 1D), gives an initial growth rate of 0.2°C s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Our HNPs have PTT conversion efficiency of 25.6% and a sharp luminescence peak at 615 nm. Recently, Sun et al [36] synthesized GNRs and gold nanostars (GNSs) with strong NIR absorption of ~800 nm 36 . They concluded that pure GNRs show a higher η value, which varies in the range 69.7–94.2%.…”
Section: Resultsmentioning
confidence: 99%
“…[38] Self-assembled WO 3−x hierarchical nanostructures ranging from 700 to 1400 nm were prepared with η 28% by Hu et al [39], and the same research group prepared CuS NPs with η 38%. [16] Although various nanostructures [16,36,39] have been evaluated as PTT agents, HNPs offer additional favorable properties that enable their use for cancer therapy. More importantly, the HNPs not only have a high η value, but also have good NIR photostability (Figure 3(D)) and fluorescence properties (Figure 2(F)).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the electromagnetic wave can easily penetrate the sharp tip structure and participate in heat production. 37 Furthermore, a previous study showed that, as a kind of electromagnetic wave, RF can induce LSPR for heat production by using gold nanostars. 38 As shown in Figure 2C, the temperatures increased with an increase in the ARs of AuNRs, demonstrating that AuNRs can be used as an RF-induced thermal-sensitive agent, and the AuNRs with the AR of 4.2:1 were selected for further research.…”
Section: Results and Discussion Characterization Of Aunrsmentioning
confidence: 99%